⎩ ⎪ ⎪ ⎨ ⎪ ⎪ ⎧ x + y + z = 4 y + 3 y + z − 7 = 3 y z − y − x = y
Given that x , y and z satisfy the system of equations above, find 2 x + 3 y + z .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
⎩ ⎪ ⎨ ⎪ ⎧ x + y + z = 4 y + 3 . . . ( 1 ) y + z − 7 = 3 y . . . ( 2 ) z − y − x = y . . . ( 3 )
( 1 ) + ( 3 )
⟹ 2 z = 5 y + 3 . . . ( 4 )
Putting ( 4 ) in ( 2 ) gives:
⟹ y = 1 1
Putting y in ( 4 ) gives:
⟹ z = 2 9
Putting y and z in ( 3 ) gives:
⟹ x = 7
⟹ 2 x + 3 y + z = ( 2 × 7 ) + ( 3 × 1 1 ) + 2 9 = 7 6 .
⎩ ⎪ ⎨ ⎪ ⎧ x + y + z = 4 y + 3 y + z − 7 = 3 y z − y − x = y ⟹ x − 3 y + z = 3 ⟹ − 2 y + z = 7 ⟹ x + 2 y − z = 0 . . . ( 1 ) . . . ( 2 ) . . . ( 3 )
( 2 ) + ( 3 ) : x = 7 . . . ( 4 )
( 1 ) + ( 3 ) : 2 x − y ⟹ y ⟹ y = 3 = 2 x − 3 = 2 × 7 ( 4 ) − 3 = 1 1 . . . ( 5 )
( 1 ) + ( 2 ) + ( 3 ) : 2 x − 3 y + z 2 x − 3 y + z + 6 y 2 x + 3 y + z ⟹ 2 x + 3 y + z = 1 0 = 1 0 + 6 y = 1 0 + 6 × 1 1 ( 5 ) = 7 6
Problem Loading...
Note Loading...
Set Loading...
1st equation
x + y + z = 4 y + 3 [Shifting y from L.H.S. to R.H.S.]
x + z = 4 y + 3 − y [Shifting z from L.H.S to R.H.S. and subtracting y from 4 y ]
x = 3 y + 3 − z
3rd equation
z − y − x = y [Putting 3 y + 3 − z in place of x ]
z − y − ( 3 y + 3 − z ) = y [Removing brackets]
z − y − 3 y − 3 + z = y [Solving L.H.S.]
2 z − 4 y − 3 = y [Shifting − 4 y from L.H.S to R.H.S.]
2 z − 3 = y + 4 y
2 z − 3 = 5 y [Shifting 5 from R.H.S to L.H.S.]
5 2 z − 3 = y
2nd equation
y + z − 7 = 3 y [Putting 5 2 z − 3 in place of y ]
5 2 z − 3 + z − 7 = 3 ( 5 2 z − 3 ) [Multiplying in R.H.S. and adding in L.H.S.]
5 2 z − 3 + 5 z − 3 5 = 5 ( 3 ∗ 2 z ) − ( 3 ∗ 3 )
5 7 z − 3 8 = 5 6 z − 9 [Removing 5 in denominator from both sides]
7 z − 3 8 = 6 z − 9 [Shifting − 3 8 and 6 z ]
7 z − 6 z = − 9 + 3 8 [Solving L.H.S and R.H.S.]
z = 2 9
Again 1st equation
x + y + z = 4 y + 3 [Putting 5 2 z − 3 in place of y ]
x + 5 2 z − 3 + z = 4 ( 5 2 z − 3 ) + 3 [Putting 29 in place of z]
x + 5 2 ( 2 9 ) − 3 + 2 9 = 5 ( 4 ∗ 2 ∗ 2 9 ) − ( 4 ∗ 3 ) + 3 [Solving it]
x + 5 5 8 − 3 + 2 9 = 5 2 3 2 − 1 2 + 3
x + 5 5 5 + 2 9 = 5 2 2 0 + 3
x + 1 1 + 2 9 = 4 4 + 3
x + 4 0 = 4 7 [Shifting 40 from L.H.S. to R.H.S.]
x = 4 7 − 4 0
x = 7
Again 1st equation
x + y + z = 4 y + 3 [Putting 7 in place of x and 29 in place of z ]
7 + y + 2 9 = 4 y + 3 [Solving it]
y + 3 6 = 4 y + 3 [Shifting y from L.H.S. to R.H.S. and 3 from R.H.S. to L.H.S.]
3 6 − 3 = 4 y − y
3 3 = 3 y [Shifting 3 from R.H.S. to L.H.S.]
3 3 3 = y
y = 1 1
Thus, x = 7 ; y = 1 1 ; z = 2 9
So, the value of 2 x + 3 y + z is
= 2 ( 7 ) + 3 ( 1 1 ) + 2 9
= 1 4 + 3 3 + 2 9
= 7 6 = A n s